Hard film forming body, machine component, and bearing
The hard film formed body with specific hardness and thickness ratios, combined with Ni and DLC layers, addresses hydrogen embrittlement and wear issues in bearings, enhancing their resistance and durability in hydrogen environments.
Patent Information
- Application Number
- CN202380041019.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-12
- Filing Date
- 2023-05-16
- Publication Date
- 2024-12-27
AI Technical Summary
Existing mechanical parts, particularly bearings, used in hydrogen environments face issues with hydrogen embrittlement, leading to early peeling and wear, and current countermeasures are either insufficient or costly.
A hard film formed body with a hard film on the substrate, characterized by a Vickers hardness ratio of 0.90 to 1.20 or a thickness of 0.1 μm to 3 μm, inhibiting hydrogen intrusion and diffusion, and optionally incorporating a Ni film, Ni-PB film, intermediate layer, and DLC layer for enhanced adhesion and wear resistance.
The hard film body provides effective hydrogen embrittlement resistance, wear resistance, and peeling resistance, suitable for bearings in hydrogen environments, while maintaining mechanical integrity and reducing material costs.
Smart Images

Figure CN119213169A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hard film formed body having a hard film on the surface of a substrate, and a mechanical component and a bearing using the hard film formed body. Background Art
[0002] In recent years, mechanical parts used in automobiles, industrial machinery, etc. have been required to be lightweight and high-strength. Such mechanical parts are often used in hydrogen intrusion environments. For example, when rolling parts such as rolling bearings or gears are used under conditions where water is mixed with lubricants or accompanied by sliding, water or lubricants decompose to generate hydrogen. This hydrogen intrusion into steel may cause early damage caused by hydrogen embrittlement.
[0003] In the past, the following technologies have been proposed as countermeasures against this hydrogen embrittlement. For example, Patent Document 1 describes a rolling part in which a steel material in a specified chemical composition range is carbonitrided and carbonitrides are dispersed and precipitated by microgranulation. Thus, a hydrogen embrittlement countermeasure is implemented for trace hydrogen from the lubricating oil. In addition, Patent Document 2 describes a hydrogen embrittlement resistant material formed of a Ni-based alloy or a Fe-Ni-based alloy, including an aging portion and a hydrogen embrittlement suppression layer exposed to hydrogen, and the tensile strength of the aging portion exceeds 1000 MPa.
[0004] In addition, a technology has been proposed to improve the wear resistance and to counter hydrogen embrittlement by forming a hard film on the surface of the substrate. For example, Patent Document 3 describes a rolling bearing having a Ni film formed on the rolling surface. In Patent Document 3, the Ni film can prevent hydrogen from invading the steel of the bearing, and the short-life peeling caused by hydrogen embrittlement can be suppressed, thereby achieving a longer life of the rolling bearing. Prior art literature
[0005] Patent Literature Patent Document 1: Japanese Patent Application Publication No. 2010-43320 Patent Document 2: Japanese Patent Application Publication No. 2010-174360 Patent Document 3: Japanese Patent Application Publication No. 2005-69273 Summary of the invention Inventions should solve problems
[0006] However, in recent years, hydrogen has attracted attention as an energy source to replace fossil fuels. When hydrogen is used as an energy source, it only produces water and does not release carbon dioxide (CO2), so it is expected to be a clean energy source. In the future, it is expected that the use of hydrogen in the whole society will make progress, and it is believed that hydrogen utilization equipment (for example, ball valves or compressors for hydrogen stations, etc.) will become popular. Mechanical parts such as bearings used in such hydrogen utilization equipment are sometimes used in an environment exposed to hydrogen. In this case, due to the presence of hydrogen supplied from the outside, it is possible to promote early peeling caused by the above-mentioned hydrogen embrittlement, and it is believed that hydrogen embrittlement countermeasures have become more important.
[0007] For example, in the above-mentioned Patent Document 1, as a countermeasure against trace hydrogen from lubricating oil, steel with a specified chemical composition range is used, but the effect may not be sufficient in an environment exposed to hydrogen such as a hydrogen atmosphere. In addition, in the above-mentioned Patent Document 3, although the rolling bearing can be appropriately used in a hydrogen atmosphere, in actual tests, only the life extension effect in a water vapor atmosphere is shown, and the effect in a hydrogen atmosphere is unclear.
[0008] On the other hand, the above-mentioned Patent Document 2 targets hydrogen embrittlement-resistant materials used in an environment exposed to hydrogen, such as high-pressure hydrogen gas piping. In the above-mentioned Patent Document 2, in order to avoid rapid functional degradation due to peeling of the surface coating, the entirety is formed of a Ni-based alloy or a Fe-Ni-based alloy, but the material cost tends to become expensive compared to general steel.
[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a hard film formed body which achieves hydrogen embrittlement resistance and wear resistance and is also excellent in peeling resistance, and a machine component and a bearing using the hard film formed body. Means of solving problems
[0010] The hard film formed body of the present invention is a hard film formed body having a hard film that inhibits the intrusion and diffusion of hydrogen atoms on the surface of a substrate, characterized in that (A) the ratio of the Vickers hardness of the hard film to the Vickers hardness of the substrate is 0.90 to 1.20, or (B) the thickness of the hard film is 0.1 μm or more and less than 3 μm. It is noted that the case where both (A) and (B) are satisfied is also included in the present invention.
[0011] The hard film-formed body satisfies the above-mentioned (A), wherein the Vickers hardness of the substrate and the Vickers hardness of the hard film are respectively 500 Hv to 1000 Hv.
[0012] The hard film formed body is characterized in that the hard film that suppresses the intrusion and diffusion of hydrogen atoms satisfies the above (A) and is a Ni film. The hard film formed body is characterized in that the Ni film includes a Ni-PB film containing 90 mass % or more of Ni.
[0013] The hard film-forming body is characterized in that, in an electrochemical hydrogen permeation method using a test piece (the thickness of the substrate is 1 mm) composed of the hard film-forming body, the area of the test piece in contact with the electrolyte solution in the cathode tank and the anode tank is set to 3.14 cm 2 , set the current density on the anode tank side to 1 mA / cm 2 Electrolysis was performed, and at this time, the extension time of the breakthrough time of the test piece was 0.4 times or more of the breakthrough time of the target piece consisting of the substrate having a thickness of 1 mm.
[0014] The hard film formed body satisfies the above-mentioned (A), and an intermediate layer and a diamond-like carbon (DLC) layer are formed on the surface of the hard film.
[0015] The hard film-forming body is characterized in that it satisfies the above (A), the ratio of the Vickers hardness is 0.95 to 1.05, and the Vickers hardness of the substrate and the Vickers hardness of the hard film are 700 Hv to 800 Hv respectively; the hard film that inhibits the intrusion and diffusion of hydrogen atoms is a Ni coating, and the Ni coating includes a Ni-PB coating containing more than 90 mass % of Ni; an intermediate layer and a diamond-like carbon layer (DLC layer) are formed on the surface of the hard film.
[0016] The hard film formed body is characterized in that the yield stress of the substrate is 1 GPa or more.
[0017] The hard film formed body satisfies the above (B), wherein the hard film that suppresses the intrusion and diffusion of hydrogen atoms is a tungsten carbide (WC) film. Furthermore, the hard film formed body is characterized in that the thickness of the WC film is not less than 0.2 μm and less than 1 μm.
[0018] The mechanical component of the present invention is characterized by using the hard film-formed body of the present invention. In addition, the mechanical component is a bearing component.
[0019] A bearing according to the present invention is characterized by using the above-mentioned bearing component. Effects of the Invention
[0020] The hard film formed body of the present invention has a hard film on the surface of a substrate that inhibits the intrusion and diffusion of hydrogen atoms, and is characterized in that (A) the ratio of the Vickers hardness of the hard film to the Vickers hardness of the substrate is 0.90 to 1.20, or (B) the thickness of the hard film is 0.1 μm or more and less than 3 μm, thereby achieving hydrogen embrittlement resistance and wear resistance while also having excellent peeling resistance.
[0021] The hard film formed body of the present invention is characterized in that the above (A) is satisfied and the Vickers hardness of the substrate and the Vickers hardness of the hard film are 500 to 1000 Hv, respectively. Therefore, it is easy to make the above ratio within a predetermined range while ensuring the wear resistance of the hard film formed body.
[0022] The hard film formed body of the present invention is characterized in that it satisfies the above-mentioned (A), the hard film is a Ni film, and in particular, the Ni film comprises a Ni-PB film containing 90 mass % or more of Ni, and thus has further excellent wear resistance.
[0023] The hard film formed body of the present invention is characterized in that it satisfies the above (A), and an intermediate layer and a DLC layer are formed on the surface of the hard film, so that the wear resistance is more excellent, and the hydrogen embrittlement resistance can be improved by these layers. In addition, by sandwiching the intermediate layer, the adhesion between the hard film and the DLC layer is improved, and the hard film formed body has excellent peeling resistance as a whole.
[0024] The hard film formed body of the present invention is characterized in that the hard film that suppresses the intrusion and diffusion of hydrogen atoms satisfies the above (B) and is a WC film. Therefore, as shown in the examples described later, although it is a thinner film than the Ni film, it can well suppress the intrusion and diffusion of hydrogen atoms. Moreover, the thickness of the WC film is 0.2 μm or more and less than 1 μm, so it becomes a hard film formed body with better peeling resistance. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a schematic cross-sectional view showing a first embodiment of the hard film formed body of the present invention. Figure 2 This is a schematic cross-sectional view showing a second embodiment of the hard film formed body of the present invention. Figure 3 This is a cross-sectional view showing an example of the bearing of the present invention. Figure 4 This is a cross-sectional view showing a hydrogen circulation pump using the bearing of the present invention. Figure 5 This is a photograph of the cross-sectional structure of the hard film-formed body of Example 1. Figure 6 is a schematic diagram of the electrochemical hydrogen permeation test. Figure 7 It is a diagram showing the outline of the electrochemical hydrogen permeation test, etc. Figure 8 This is a photograph of the cross-sectional structure of the hard film-forming body of Example 3. Fig. 9 It is a graph showing the behavior of ionization current in Examples and Comparative Examples. Fig.10 It is a graph showing the behavior of ionization current in Examples and Comparative Examples. DETAILED DESCRIPTION
[0026] The hard film formed body of the present invention is described below with reference to the accompanying drawings. The hard film formed body of the present invention is used for mechanical parts, etc., and in particular, for bearings, etc. used in a hydrogen intrusion environment. The hydrogen intrusion environment refers to an environment in which various forms of hydrogen, such as hydrogen gas or moisture in the use environment, and hydrogen atoms in lubricating oil, can intrude and diffuse into the substrate.
[0027] (First embodiment) Figure 1 Schematic cross-sectional view of the first embodiment of the hard film forming body of the present invention. Figure 1 As shown, the hard film-formed body 1 includes a substrate 2 and a hard film 3 formed on the surface of the substrate 2. The hard film 3 has a property of suppressing the intrusion and diffusion of hydrogen atoms, for example, delaying the intrusion and diffusion of hydrogen into the substrate 2. As a result, the occurrence of hydrogen embrittlement of the substrate 2 can be delayed. The hard film 3 is formed of a material different from that of the substrate 2.
[0028] In the present invention, (A) the ratio of the Vickers hardness of the hard film 3 to the Vickers hardness of the substrate 2 (Vickers hardness (Hv) of the hard film 3 / Vickers hardness (Hv) of the substrate 2; hereinafter, also referred to as the hardness ratio) is 0.90 to 1.20, or (B) the thickness of the hard film 3 is 0.1 μm or more and less than 3 μm. Therefore, the hard film 3 has excellent adhesion to the substrate 2, and the hydrogen embrittlement resistance and wear resistance of the hard film 3 can be stably exerted. When (A) is satisfied, the hardness ratio is preferably 0.90 to 1.10, more preferably 0.95 to 1.05, and further preferably 0.98 to 1.02. In addition, the hardness ratio may be greater than 1.00.
[0029] As the substrate 2, any commonly used steel material can be used. For example, high carbon chromium bearing steel (SUJ1, SUJ2, SUJ3, SUJ4, SUJ5, etc.; JIS G 4805), carburizing steel (SCr420, SCM420, etc.; JIS G 4053), stainless steel (SUS440C, etc.; JIS G4303), etc. As the substrate 2, special materials or heat treatment for hydrogen embrittlement may not be performed.
[0030] The Vickers hardness of the substrate 2 (the Vickers hardness of the surface on which the hard film 3 is formed) is preferably 500 Hv to 1000 Hv, more preferably 600 Hv to 900 Hv, and further preferably 700 Hv to 800 Hv. By setting it within these ranges, while ensuring the wear resistance of the hard film-forming body, it is easy to make the hardness ratio in the (A) feature within a specified range.
[0031] Before forming the hard film 3, the substrate 2 may be cured by heat treatment. In addition, the nitrided layer may be formed by nitriding treatment. As the nitriding treatment, for example, a plasma nitriding treatment may be performed to make it difficult for an oxide layer that hinders adhesion to be formed on the surface of the substrate. In addition, in order to improve the adhesion of the hard film 3 to the substrate 2, the substrate 2 may be pretreated. As the pretreatment, for example, degreasing treatment using a solvent or an alkaline solution, acid immersion treatment, etc. may be mentioned.
[0032] The surface roughness Ra of the substrate 2 is, for example, 0.1 μm or less, or preferably 0.05 μm or less. In order to adjust the surface roughness Ra of the substrate 2 , various processing (surface finishing, etc.) may be performed.
[0033] The higher the strength of the steel, the greater the impact of hydrogen embrittlement, especially in the form called delayed fracture. Hydrogen embrittlement is significant in high-strength steel with a yield stress of 1 GPa or more, but for the hard film-formed body of the present invention, by forming the following hard film or DLC layer on the surface of the steel, it is possible to appropriately suppress the delayed fracture caused by hydrogen embrittlement.
[0034] The hard film 3 may be any film that suppresses the intrusion and diffusion of hydrogen atoms, and examples thereof include: a Ni film with Ni as the main component, a Cu film with Cu as the main component, a Zn film with Zn as the main component, a WC film, and combinations thereof. Among these films, the hard film 3 is preferably a Ni film or a WC film because it can further delay the intrusion and diffusion of hydrogen such as hydrogen gas and moisture in the use environment and hydrogen atoms in the lubricating oil into the substrate 2. Furthermore, in the configuration satisfying (A), the hard film 3 is preferably a Ni film, and in the configuration satisfying (B), the hard film 3 is preferably a WC film.
[0035] For example, as the Ni film, a Ni-P film, a Ni-B film, a Ni-PB film, a Ni-PB-SiC dispersed film, and a combination thereof can be used. These Ni films are formed by a plating method such as a PVD method (physical vapor deposition method) such as an ion plating method or a sputtering method, an electrolytic plating method, or an electroless plating method. For example, in the case of an electroless plating method, a plating bath containing various reducing agents in a nickel salt can be used to form an electroless plated film. In particular, the hard film 3 is preferably a Ni-plated film (nickel-plated film), and the Ni-plated film preferably contains a Ni-PB film.
[0036] The Ni-PB coating is a composite coating of Ni, P, and B, formed by a non-electrolytic plating method. In the Ni-PB coating, the content of Ni is, for example, 90% by mass or more, preferably 95% by mass or more, and more preferably 97% by mass or more. As the composition of the Ni-PB coating, it is particularly preferred that Ni is 97% by mass or more, P is 1% to 3% by mass, and B is 1% by mass or less. It should be noted that the composition can be appropriately adjusted according to the characteristics required of the coating. For example, the Ni-PB coating is harder than the Ni-P coating and has better wear resistance. As a commercially available product of the Ni-PB coating, for example, there can be cited: Kaniboron (trade name) manufactured by Japan Kanize Co., Ltd.
[0037] Regarding the relationship between the heat treatment temperature and hardness after the electroplating treatment, for the Ni-PB coating, in the range below 400°C, the higher the heat treatment (baking) temperature, the higher the hardness of the coating. This is because the crystallization of Ni is carried out through the heat treatment. The structure of the Ni-PB coating is microcrystalline (polycrystalline), and the peak from Ni can be observed through the X-ray diffraction pattern. In addition, the Ni-PB coating is harder than the NP coating, and the Vickers hardness is Hv700 or more when precipitated, and the Vickers hardness is Hv800 or more when heat treated at 200°C.
[0038] In the configuration satisfying (A), the Vickers hardness of the hard film 3 is preferably 500 Hv to 1000 Hv, more preferably 600 Hv to 900 Hv, and even more preferably 700 Hv to 800 Hv.
[0039] For example, in the case where the hard film 3 contains a Ni-PB coating, the higher the heat treatment temperature, the higher the hardness of the coating. On the other hand, the hardness of the substrate 2 obtained by quenching or the like decreases, and the overall strength of the hard film formation body may decrease. Therefore, using a steel material that has been solidified by heat treatment, the Ni-PB coating provided on the surface is subjected to an aging treatment at an appropriate temperature, thereby achieving both a strong steel material and a hard film, and obtaining a hard film formation body that has strength as a whole. Furthermore, even when the steel material is deformed, it is possible to suppress the yielding, plastic deformation, and peeling of only the hard film. It should be noted that, depending on the hardness of the steel material, aging treatment may not be necessary.
[0040] For example, by setting the baking temperature of the Ni-PB coating to 200°C or less, preferably 180°C or less, the influence of tempering of the substrate 2 can be reduced. Thus, in the manufacture of the hard film 3, it is preferred to appropriately select the baking temperature of the Ni-PB coating according to the tempering temperature and required strength of the substrate 2, the hardness required of the hard film 3 on its surface, and the difference between the hardness of the substrate 2 and the hard film 3, so as to avoid any adverse conditions.
[0041] In the configuration satisfying (A), the lower limit of the thickness of the hard film 3 is preferably 1 μm, taking into account the ease of management in manufacturing and the possibility of thickness reduction due to wear. On the other hand, in order to suppress fluctuations in manufacturing costs, processing time, and stress within the film, the upper limit of the thickness of the hard film 3 is preferably 50 μm. The thickness of the hard film 3 is more preferably 3 μm to 30 μm, and further preferably 3 μm to 10 μm. The thickness can be set according to the desired effect of hydrogen embrittlement resistance, etc. In addition, the thickness can be adjusted by adjusting the immersion time in the plating bath, for example, in the case of plating.
[0042] In the configuration satisfying (B), the WC film is formed, for example, by an unbalanced magnetron sputtering (UBMS) method using a WC target. The thickness of the WC film is preferably 0.2 μm or more and less than 1 μm, and may be 0.2 μm or more and 0.6 μm or less. In addition, the Vickers hardness of the WC film is not particularly limited, and may be, for example, 1000 Hv to 2000 Hv, or may be a hardness exceeding 2000 Hv.
[0043] The hydrogen diffusion coefficient in the hard film 3 is preferably 5.00×10 -12 m 2 / s or less, can be 1.00×10 -12 m 2 / s or less, or 8.00×10 -13 m 2 / s or less. The specific range is, for example, 1.00×10 -13 m 2 / s~8.00×10 -13 m 2 / s. The hydrogen diffusion coefficient is obtained by electrochemical hydrogen permeation method. The details are shown in the examples.
[0044] As an example of a method for forming the hard film 3, the formation of a Ni-PB coating is described. The plating bath used is a plating bath containing a phosphorus compound and a boron compound as a reducing agent in a nickel salt. More specifically, as the nickel salt, nickel chloride, nickel sulfate, etc. can be used, as the phosphorus compound, sodium hypophosphite, potassium hypophosphite, etc. can be used, and as the boron compound, dimethylaminoborane, sodium borohydride, etc. can be used. The ratio of the nickel salt, phosphorus compound and boron compound in the plating bath can be appropriately adjusted according to the composition of the obtained plated film. It should be noted that an organic acid such as acetic acid or a chelating agent such as ethylenediaminetetraacetic acid (EDTA) can also be added to the plating bath.
[0045] From the viewpoint of stability and precipitation rate, the pH of the plating bath is preferably in the range of 6 to 7. The temperature of the plating bath is, for example, 60 to 90°C, and preferably 70 to 90°C.
[0046] The film hardness can be increased by heat treating (baking) the obtained plated film. The heat treatment temperature is, for example, 100°C to 200°C, preferably 100°C to 180°C, and more preferably 120°C to 160°C. The heat treatment time is, for example, 30 minutes to 120 minutes. The heat treatment is performed in an atmosphere of air, an inert gas, a reducing gas, or the like.
[0047] As the physical properties of the hard film formed body 1, in an electrochemical hydrogen permeation method using a test piece composed of the hard film formed body (the thickness of the substrate 2 was 1 mm), the area of the test piece in contact with the electrolyte solution in the cathode tank and the anode tank was set to 3.14 cm 2 , set the current density on the anode tank side to 1 mA / cm 2 When electrolysis is performed, the extension time of the penetration time of the test piece is 0.4 times or more, more preferably 1.0 times or more, further preferably 2.0 times or more, 5.0 times or more, or 10.0 times or more of the penetration time of the target piece composed of the substrate 2 with a thickness of 1 mm. It should be noted that the details of the electrochemical hydrogen permeation method are described in the examples.
[0048] (Second embodiment) Figure 2 Schematic cross-sectional view of the second embodiment of the hard film forming body of the present invention. Figure 2 As shown, the hard film formation body 4 includes: a substrate 5, a hard film 6 formed on the surface of the substrate 5, an intermediate layer 7 formed on the hard film 6, and a DLC layer 8 formed on the intermediate layer 7. In this case, the coating formed on the substrate 5 has a three-layer structure. It is to be noted that the configuration of the substrate 5 and the hard film 6 is the same as that of the substrate 2 and the hard film 3 described in the first embodiment (particularly the configuration satisfying (A)), and therefore the description thereof is omitted.
[0049] The intermediate layer 7 is a layer between the hard film 6 and the DLC layer 8. As the intermediate layer 7, a tungsten carbide (WC) layer, a mixed layer mainly composed of WC and DLC, etc. can be used. WC has a hardness and elastic modulus intermediate between the hard film 6 and the DLC layer 8, and is not prone to concentration of residual stress after film formation.
[0050] As the intermediate layer 7, it is preferred that the mixed layer is mainly composed of WC and DLC, and further, it is more preferred that the content of WC in the intermediate layer decreases and the content of DLC in the intermediate layer increases in a continuous or stepwise manner from the hard film 6 side to the DLC layer 8 side. As a result, the adhesion between the two surfaces of the hard film 6 and the DLC layer 8 is excellent. In addition, in the intermediate layer, WC and DLC form a physically bonded structure, which can prevent damage in the intermediate layer. Furthermore, since the DLC content is increased on the DLC layer 8 side, the adhesion between the DLC layer 8 and the intermediate layer 7 is excellent. In this case, the intermediate layer 7 becomes a layer in which the DLC with high non-adhesiveness is bonded to the hard film 6 side by the anchoring effect of WC.
[0051] The DLC layer 8 is a film mainly composed of DLC. DLC has a graphite structure (sp 2 ) and diamond structure (sp 3 ) An intermediate structure of the two mixed. As a method for forming the DLC layer 8, a physical vapor deposition method such as a sputtering method or an ion plating method, a chemical vapor deposition method, a UBMS method, etc. can be used.
[0052] As the DLC layer 8, it is preferred to have a relaxation layer portion (not shown) on the adjacent side to the intermediate layer 7. This is a portion obtained by changing at least one of these parameters continuously or in stages in order to avoid a sudden change in the film forming condition parameters (hydrocarbon gas introduction amount, vacuum degree, bias voltage) of the intermediate layer 7 and the DLC layer 8, for example, when these parameters are different in the UBMS method. More specifically, starting from the film forming condition parameters when the outermost layer of the intermediate layer 7 is formed and ending at the final film forming condition parameters of the DLC layer 8, each parameter is changed continuously or in stages within the range. As a result, the sharp difference in physical properties (hardness, elastic modulus, etc.) between the intermediate layer 7 and the DLC layer 8 disappears, and the adhesion between the intermediate layer 7 and the DLC layer 8 is better. For example, by increasing the bias voltage continuously or in stages, the graphite structure (sp 2 ) and diamond structure (sp 3 )'s composition ratio tends to the latter, and the hardness tends to increase.
[0053] In the hard film formed body 4 of the second embodiment, the Vickers hardness of the DLC layer 8 serving as the surface layer is, for example, 1000 Hv to 3000 Hv.
[0054] The total film thickness of the intermediate layer 7 and the DLC layer 8 is preferably 1.0 μm to 5.0 μm, and more preferably 1.0 μm to 3.0 μm. By setting it within these ranges, the wear resistance and mechanical strength can be improved, and the peeling of the intermediate layer 7 and the DLC layer 8 can be suppressed. In addition, the total film thickness of the intermediate layer 7 and the DLC layer 8 is preferably smaller than the film thickness of the hard film 6. In the hard film formation body 4, the total thickness of the film formed on the substrate 5 is preferably 3.0 μm to 30 μm, and more preferably 3.0 μm to 10 μm.
[0055] As an example of a method for forming the intermediate layer 7 and the DLC layer 8, an example of a UBMS apparatus using Ar gas as a sputtering gas will be described.
[0056] For example, when the intermediate layer 7 is a mixed layer mainly composed of WC and DLC, by forming a film while continuously or stepwise increasing the sputtering power applied to the graphite target as a carbon supply source and continuously or stepwise decreasing the power applied to the WC target, a layer with an inclined composition in which the content of WC decreases toward the DLC layer 8 side and the content of DLC increases toward the DLC layer 8 side can be formed. The vacuum degree in the UBMS device (inside the film forming chamber) during the film formation of the intermediate layer 7 is, for example, 0.2 to 1.2 Pa. In addition, the bias voltage applied to the substrate is, for example, 20 to 100 V.
[0057] Regarding the DLC layer 8, a graphite target and a hydrocarbon gas (methane gas, acetylene gas, benzene, etc.) are used as a carbon supply source, and the ratio of the amount of the hydrocarbon gas introduced into the above-mentioned device to the amount of Ar gas introduced into the above-mentioned device 100 is set to, for example, 1 to 15, so that carbon atoms generated by the carbon supply source can be deposited on the intermediate layer 7 to form a film. The vacuum degree in the device is, for example, 0.2 to 0.9 Pa.
[0058] In the above Figure 2 In the embodiment of the present invention, the intermediate layer 7 is interposed between the hard film 6 and the DLC layer 8, and the intermediate layer 7 can be omitted. Figure 1 and the above Figure 2 For example, the intermediate layer 7 and the DLC layer 8 may be repeatedly stacked on the hard film 6. In addition, the DLC layer may be formed on the surface of the hard film having the structure satisfying (B) described in the first embodiment. In this case, for example, the hard film-forming body has a substrate, a WC film formed on the surface of the substrate, and a DLC layer formed on the WC film.
[0059] (Application of hard film forming body) The use of the hard film forming body of the present invention is not particularly limited, but due to its excellent mechanical properties, it is preferably used in mechanical parts. As mechanical parts, there can be mentioned: mechanical parts used for rolling parts or sliding parts of the device, etc., specifically, there can be mentioned: sliding parts, bearing parts, rolling rollers, compressor blades, engine parts such as gas turbine blades, cutting tools (chips), gears, etc. As bearing parts, there can be mentioned: track wheels such as inner and outer wheels, rolling elements for bearings, retainers, etc. The bearing of the present invention is a bearing in which the hard film forming body of the present invention is used as a bearing part. As bearings, for example, there can be mentioned: rolling bearings, sliding bearings (spherical bushings, etc.), direct-acting guide bearings, ball screws, direct-acting bearings, etc.
[0060] based on Figure 3 An example of the bearing of the present invention will be described. Figure 3 A cross-sectional view of a deep groove ball bearing using the hard film forming body of the first embodiment as a rolling element is shown. The deep groove ball bearing 11 has an inner ring 12 having an inner ring raceway surface 12a on the outer circumference, an outer ring 13 having an outer ring raceway surface 13a on the inner circumference, and a plurality of balls (rolling elements) 14 rolling between the inner ring raceway surface 12a and the outer ring raceway surface 13a. The balls 14 are kept at a certain interval by a retainer 15. The axial end openings of the inner and outer rings are sealed by a sealing member 16, and grease 17 is sealed in the bearing space.
[0061] exist Figure 3 In the rolling bearing, a hard film 18 is formed on the entire spherical surface of the ball 14. Figure 3 In the embodiment, the hard film 18 is formed only on the ball 14, but it can also be formed on the surface (including part) of other bearing components such as the inner ring 12 and the outer ring 13 according to the bearing form or its use. In a structure where two or more components are in contact or sliding, it is preferred that a hard film forming body is used for one or more of the components.
[0062] At least a portion of the bearing components of the bearing of the present invention is formed of the hard film-forming body of the present invention, so that early peeling caused by hydrogen embrittlement when used in a hydrogen intrusion environment can be appropriately suppressed. Therefore, the bearing of the present invention is suitable for bearings used in an environment where early peeling caused by hydrogen embrittlement is likely to occur.
[0063] For example, it can be used as a bearing for a drive axle of a vehicle (fuel cell vehicle (FCV), electric vehicle (EV), etc.), a vehicle transmission (continuously variable transmission, etc.), and a vehicle engine (drive device, transmission). Bearings for these uses are required to be able to withstand the rapid changes in rotation speed associated with speed change, high rotation, and high load performance. In addition, for these devices, low-viscosity lubricants are used to reduce power loss. In such a harsh use environment, sliding easily promotes wear of the rail wheels or rolling elements. If a new surface of the steel is formed due to this wear, water or lubricant components decompose to produce hydrogen, which invades the steel, so early peeling caused by hydrogen embrittlement is likely to occur. In addition, in fuel cell vehicles, etc., it is believed that leaked hydrogen from hydrogen equipment may contribute to hydrogen embrittlement of rolling bearings.
[0064] In addition, the bearing of the present invention is used as a bearing for hydrogen utilization equipment. In particular, it is useful as a bearing used in an environment exposed to hydrogen supplied from the outside. In the future, due to the advancement of hydrogen utilization, it is expected that the use of bearings in a hydrogen atmosphere (including a mixed atmosphere mixed with hydrogen) will increase. In this case, in addition to the hydrogen generated by the decomposition of the grease (hydrogen as an internal factor), hydrogen supplied from the outside (hydrogen as an external factor) will also affect the early peeling caused by hydrogen embrittlement. Compared with the past, the bearing of the present invention can effectively suppress early peeling by using a hard film forming body even in the case of more concern about early peeling due to hydrogen embrittlement.
[0065] As hydrogen utilization equipment, for example, a ball valve or a compressor for a hydrogen station can be cited. The type of the compressor is not particularly limited, and it can be any of reciprocating (reciprocating), rotary (screw), centrifugal, and axial flow. In addition, the hydrogen utilization equipment also includes the above-mentioned high-pressure hydrogen pressure reducing valve for fuel cell vehicles, hydrogen circulation pumps, etc.
[0066] Here, as a configuration in which the bearing of the present invention is applied to a hydrogen circulation pump, Figure 4 The hydrogen circulation pump 21 includes a motor housing 22 , a pump housing 23 , rotating shafts 24 , 25 , a motor stator 26 , a motor rotor 27 , gears 28 , 29 , rotors 30 , 31 , and rolling bearings 32 , 33 , 34 , 35 , 36 , 37 .
[0067] The engine housing 22 is mounted on the pump housing 23. One end side of the rotating shaft 24 is arranged in the engine housing 22, and the other end side of the rotating shaft 24 is arranged in the pump housing 23. One end and the other end of the rotating shaft 24 are rotatably supported by a rolling bearing 32 arranged in the engine housing 22 and a rolling bearing 33 arranged in the pump housing 23, respectively. In addition, the rotating shaft 24 is rotatably supported between one end and the other end by a rolling bearing 34 and a rolling bearing 35 arranged in the pump housing 23.
[0068] The rotating shaft 25 is disposed in the pump housing 23. One end of the rotating shaft 25 is rotatably supported by a rolling bearing 36 disposed in the pump housing 23. The rotating shaft 25 is rotatably supported by a rolling bearing 37 disposed in the pump housing 23 at a position away from the one end.
[0069] The engine stator 26 is arranged in the engine case 22. The engine rotor 27 is mounted on the rotating shaft 24 in a manner opposite to the engine stator 26. The rotating shaft 24 rotates by the engine stator 26 and the engine rotor 27. The gear 28 and the gear 29 are mounted on the rotating shaft 24 and the rotating shaft 25, respectively. The rotation of the rotating shaft 24 is transmitted to the rotating shaft 25 by the gear 28 and the gear 29. It should be noted that the gear 28 is located between the rolling bearing 34 and the rolling bearing 35, and the gear 29 is located between the rolling bearing 36 and the rolling bearing 37.
[0070] A pump chamber 23a is formed in the pump housing 23. A rotor 30 and a rotor 31 are arranged in the pump chamber 23a. The rotor 30 and the rotor 31 are respectively mounted on the rotating shaft 24 and the rotating shaft 25. The rotor 30 rotates with the rotation of the rotating shaft 24, and the rotor 31 rotates with the rotation of the rotating shaft 25, thereby hydrogen is sucked into the pump chamber 23a and hydrogen is ejected from the pump chamber 23a.
[0071] exist Figure 4 In the embodiment, rolling bearings 32, 33, 34, and 36 are deep groove ball bearings. It should be noted that rolling bearing 33 is used in an environment exposed to hydrogen supplied from the outside (e.g., in a hydrogen atmosphere). Rolling bearings 35 and 37 are multi-row angular contact ball bearings. Figure 4 In the configuration of , at least one of the rolling bearings 32, 33, 34, 35, 36, and 37 is used as the bearing of the present invention. Example
[0072] The present invention is specifically described by way of Examples and Comparative Examples, but the present invention is not limited to these Examples at all.
[0073] [Examples 1-2, Comparative Example 1] After quenching SUJ2 with a thickness of about 1 mm, it is tempered at 190°C to prepare a steel plate with a hardness of 61.5HRC (730Hv). Regarding Examples 1 to 2, a nickel-phosphorus-boron (kaniboron) treatment as a type of electroless plating method is performed on the surface of the steel plate. The composition of the coating thus obtained is: Ni: 97% to 98% by mass, P: 1.5% to 2.5% by mass, B: 0.05% to 0.5% by mass. After the nickel-phosphorus-boron plating treatment, it is baked at 150°C for 1 hour for aging curing to form an electroless Ni-PB plating film as a hard film. The thickness of the Ni-plated coating is 5μm (Example 1) and 30μm (Example 2). Figure 5 The cross-sectional structure photograph of the hard film formed body of Example 1 is shown. Strictly speaking, the Ni-plated film is a structure in which an electroless Ni-P-plated film is formed on a substrate, and an electroless Ni-PB-plated film is formed thereon (on the outermost surface). In Comparative Example 1, the above-mentioned plating treatment is not performed, and a SUJ2 steel sheet that has been quenched and tempered is used.
[0074] <Hardness test> The Vickers hardness of the hard film of each test piece of Examples 1 to 2 was measured according to JIS Z 2244. As a result, the hardness of the hard film in Example 1 was 724 Hv, and the hardness of the hard film in Example 2 was 735 Hv. These hardnesses are roughly the same as the hardness of SUJ2 (substrate). In addition, the ratio of the Vickers hardness of the hard film to the Vickers hardness of the substrate is shown in Table 1. It should be noted that the yield stress of the substrate is about 1200 to 1700 MPa.
[0075] [Table 1] Film structure Hardness of the substrate Hardness of hard film Hardness ratio Comparative Example 1 SUJ2 730Hv - - Example 1 SUJ2+Ni plating film 5μm 730Hv 724Hv 0.99 Example 2 SUJ2+Ni plating film 30μm 730Hv 735Hv 1.01
[0076] <Electrochemical Hydrogen Permeation Test> As an evaluation of hydrogen intruding and diffusing into each test piece of Examples 1 and 2 and Comparative Example 1, an electrochemical hydrogen permeation test was performed. Figure 6 is a schematic diagram of the test device. Figure 6 As shown, the test device 41 includes a cathode tank 42, an anode tank 45, a cathode electrode 44 (e.g., a Pt electrode), an anode electrode 47 (e.g., a Pt electrode), a constant current meter, and a constant potential meter. The cathode tank 42 and the anode tank 45 are separated by a test piece 51. In Examples 1 and 2, the hard film formed on the test piece 51 is arranged to be located on the cathode tank 42 side.
[0077] The cathode tank 42 contains an electrolyte solution 43, in which a cathode electrode 44 is immersed. The anode tank 45 contains an electrolyte solution 46, in which an anode electrode 47 is immersed. In this test, an aqueous solution obtained by mixing thiouric acid in 0.1N sulfuric acid is used as the electrolyte solution 43, and a 1N sodium hydroxide aqueous solution is used as the electrolyte solution 46. The constant current meter is connected to the cathode electrode 44 and the test piece 51. The constant potential meter is connected to the anode electrode 47, the test piece 51 and the reference electrode 49 (for example, an Ag / AgCl electrode). The reference electrode 49 is immersed in a saturated KCl aqueous solution 48 and is connected to the anode tank 45 through a salt bridge 50.
[0078] In the test device 41, a constant current meter is used to apply a predetermined potential between the test piece 51 and the cathode electrode 44 for electrolysis, thereby generating hydrogen on the surface of the test piece 51 on the cathode slot 42 side. The generated hydrogen invades the interior of the test piece 51 from the surface on the cathode slot 42 side. On the other hand, the surface potential of the test piece 51 is maintained at a potential at which hydrogen atoms are oxidized into hydrogen ions by the constant potential meter. As a result, hydrogen atoms that invade from the cathode slot 42 and diffuse in the test piece 51 and reach the surface on the anode slot 45 side are rapidly oxidized into hydrogen ions, generating an ionized current. In this test, the breakthrough time method is used, in which the diffusion coefficient is calculated based on the time until the ionization current begins to increase. Specifically, the time from the start of the test to the start of the increase in the ionization current (breakthrough time) is set to tb, the thickness of the test piece 51 is set to L (the total thickness of the substrate and the hard film), and the diffusion coefficient D is calculated according to the following formula (1): H (Reference: Takahiro Kushida, "Study on Hydrogen Embrittlement Using Electrochemical Hydrogen Permeation Method", Materials and Environment, 2000, Vol. 49, p. 195-200) It should be noted that the diffusion coefficient was measured in the range of 20°C to 25°C.
[0079] [Number 1]
[0080] Specifically, the area of the test piece 51 in contact with the electrolyte solutions 43 and 46 in the cathode tank 42 and the anode tank 45 was set to 3.14 cm 2 , the current density on the anode tank 45 side is set to 1 mA / cm 2 Electrolysis was performed, and the ionization current on the cathode side was measured in units of 0.1 μA to determine the increase in the ionization current. Average values of the penetration time and the diffusion coefficient D of Examples 1 to 2 and Comparative Example 1 H The average values are shown in Table 2.
[0081] [Table 2]
[0082] As shown in Table 2, compared with Comparative Example 1 (SUJ2 with a thickness of 1 mm), Examples 1 and 2 in which the Ni-plated film is formed have thicknesses increased by about 0.5% and 3%, respectively, but the penetration time is extended by 41% and 269%, respectively. In addition, the diffusion coefficient D calculated by the penetration time method is H Compared with Comparative Example 1, Example 1 was 75%, and Example 2 was 31%. The results show that the Ni plating film inhibits the intrusion and diffusion of hydrogen.
[0083] In addition, the deviation (2σ) of the penetration time of Comparative Example 1 is the largest, which is about ±26%. In contrast, the deviation (2σ) of the penetration time of Example 1 is ±6%, and the deviation (2σ) of the penetration time of Example 2 is ±2%. It should be noted that in the t-test, the significance level of the penetration time between Comparative Example 1 and Examples 1-2 is 1%, and there is a significant difference. The diffusion coefficient D calculated from the penetration time is H The significance level was 5%, indicating a significant difference.
[0084] The penetration time of Examples 1 to 2 and Comparative Example 1 is a measure of the time it takes for hydrogen atoms to diffuse from the surface of the hard film-forming body to a position 1 mm deep.
[0085] In addition, the hydrogen diffusion coefficient of Comparative Example 1 obtained by the electrochemical hydrogen permeation method is 3.16×10 -11 m 2 / s and the penetration time, as well as the penetration time of Example 1 and Example 2, the hydrogen diffusion coefficient of the Ni-plated film was estimated by the finite element method. The result was that the hydrogen diffusion coefficient of the Ni-plated film of Example 1 was 4.95×10 -13 m 2 / s, the hydrogen diffusion coefficient of the Ni-plated film of Example 2 is 2.84×10 -13 m 2 / s. Originally, the values are consistent regardless of the film thickness, but differences occur due to measurement errors, variations in film thickness, etc. The method of estimating the hydrogen diffusion coefficient by the finite element method is as follows. (1) The concentration on one side of a 1 mm plate was set to 1, and the hydrogen diffusion coefficient of Comparative Example 1 was used to analyze the concentration diffused to the opposite side after the "penetration time" (assuming this to be the detection lower limit concentration). (2) Assign concentration 1 to one side of the plate and the hydrogen diffusion coefficient of comparison example 1 to the SUJ2 portion. The hydrogen diffusion coefficient of the coated portion is appropriately varied as an unknown variable, and the analysis is repeated so that the concentration diffused to the opposite surface after the "penetration time" of comparison example 1 becomes the concentration calculated in the above (1).
[0086] In the above electrochemical hydrogen permeation test, thiourea was added to the electrolyte solution on the cathode side. Figure 7 As shown in (a), it is believed that: by hindering the hydrogen atoms (H ad ) and then combine to form H2, etc. ad →H ab In the invasion reaction, H ad It is also speculated that there is a surplus of H ad When along H 2adOn the other hand, when hydrogen is used to penetrate the test piece or when performing strength tests such as fatigue, the dissociative adsorption reaction of hydrogen molecules is suppressed ( or ), and can also delay the intrusion and diffusion of hydrogen, preventing the reduction of strength caused by hydrogen embrittlement (refer to Figure 7 (b)). However, in this case, if the hydrogen supply source is not hydrogen molecules but hydrogen atoms or hydrogen ions in a certain molecule, the countermeasure for hydrogen embrittlement may not be effective. Therefore, in order to cope with not only hydrogen gas but also various hydrogen supply sources such as moisture in the use environment and hydrogen atoms in lubricating oil, in this embodiment, an electrochemical hydrogen permeation test focusing on hydrogen intrusion and diffusion was used for evaluation.
[0087] [Example 3] The surface of the quenched and tempered steel sheet was subjected to nickel-phosphorus-boron plating in the same manner as in Example 1 to form a 5 μm thick Ni plating layer, a WC / DLC film was further formed thereon as an intermediate layer, and a DLC film was formed on the outermost surface.
[0088] The WC / DLC coating is formed by the UBMS method. Specifically, while supplying methane gas as a hydrocarbon gas, the sputtering power applied to the WC target and the graphite target is adjusted to tilt the composition ratio of WC and DLC, forming a WC / DLC tilted layer with more WC on the Ni-plated coating side and more DLC on the surface side. In addition, the DLC coating is also formed by the UBMS method. At this time, a graphite target and biogas as a hydrocarbon gas are used as a carbon supply source. Figure 8 A photograph showing the cross-sectional structure of the hard film-formed body of Example 3 is shown.
[0089] Next, an electrochemical hydrogen permeation test was performed on the test piece of Example 3. Here, in the electrochemical hydrogen permeation test, it is necessary to flow current through the surface of the test piece or measure current. However, in the test piece of Example 3, the surface on the cathode slot side where hydrogen is generated and invaded is a DLC coating, and the resistance is extremely high, so it is difficult to perform an electrochemical hydrogen permeation test in the same operation as above. Therefore, a gold vapor-deposited film of about several nm is formed on the DLC coating to reduce the resistance value of the outermost surface, thereby performing an electrochemical hydrogen permeation test. In addition, in order to confirm whether there is the ability to prevent hydrogen permeation of the gold vapor-deposited film, a test piece (Comparative Example 2) having the same gold vapor-deposited film as in Example 3 formed on the surface of SUJ2 is used as a comparison object. The test conditions are the same as those of Examples 1 to 2 and Comparative Example 1. The results are shown in Table 3.
[0090] [Table 3] 1) In the case of the electrochemical hydrogen permeation test, a gold vapor-deposited film of about several nanometers is formed on the outermost surface of each test piece.
[0091] From the comparison of Comparative Example 2 in Table 3 and Comparative Example 1 in Table 2, it can be seen that the ability of the gold vapor-deposited film to prevent hydrogen penetration is very small. As shown in Table 3, compared with Comparative Example 2, Example 3 in which a Ni-plated film, a WC / DLC film, and a DLC film are formed greatly prolongs the penetration time and greatly reduces the diffusion coefficient D H It should be noted that the hydrogen diffusion coefficient of the WC / DLC film and the DLC film is smaller than that of the Ni-plated film and is estimated to be 1.00×10 -15 m 2 / s~1.00×10 -14 m 2 / s (specifically, about 1.18×10 -15 m 2 / s).
[0092] The results of Example 3 are more significant than those of Examples 1 and 2. It is known that the WC / DLC film and the DLC film also suppress the intrusion and diffusion of hydrogen, and that the effect of the Ni plating film can be significantly enhanced by forming these films on the Ni plating film.
[0093] Fig. 9 The results of Examples 1 to 3 and Comparative Examples 1 to 2 are summarized in a graph. Fig. 9 As shown, by forming a Ni plating film as a hard film on the surface of the substrate, the hydrogen embrittlement delay effect can be exerted.
[0094] [Example 4] A 0.4 μm thick WC film was formed by unbalanced magnetron sputtering (UBMS) using a WC target on the surface of 1 mm thick SUJ2 (730 Hv) that had been quenched and tempered in Comparative Example 1. The Vickers hardness of the WC film was 1000 Hv to 2000 Hv.
[0095] The obtained test piece of Example 4 was subjected to an electrochemical hydrogen permeation test. The test conditions were the same as those of Examples 1 to 2 and Comparative Example 1. The results are shown in Tables 4 and Fig.10 shown.
[0096] [Table 4]
[0097] As shown in Table 4 and Fig.10 As shown in FIG. 1 , compared with Comparative Example 1, Example 4 in which a WC film is formed has a significantly longer penetration time and a significantly lower diffusion coefficient D H It should be noted that the hydrogen diffusion coefficient of the WC film was estimated by finite element method (FEM) analysis based on the average value in Table 4, and the result was estimated to be 3.37×10 -12 m2 / s. In addition, the results of the WC film of Example 4 are more significant than the results of the Ni-plated films of Examples 1 and 2. Thus, by forming the WC film as a hard film on the surface of the substrate, the hydrogen embrittlement delay effect can also be well exerted. Industrial Applicability
[0098] The hard film formed body of the present invention has excellent peeling resistance while achieving hydrogen embrittlement resistance and wear resistance, and can therefore be suitably used in mechanical parts such as bearings used in a hydrogen intrusion environment.
[0099] Description of Reference Numerals 1 Hard film forming body 2. Substrate 3 Hard film 4 Hard film forming body 5. Substrate 6 Hard film 7 Middle Layer 8 DLC Tiers 11 Deep groove ball bearings (bearings) 12 Inner circle 13 Outer ring 14 Balls (rolling elements) 15 Retainer 16 Sealing parts 17 Grease 18 Hard film 21 Hydrogen circulation pump 22 Engine housing 23 Pump housing 24, 25 Rotation axis 26 Engine stator 27 Engine rotor 28, 29 Gear 30, 31 Rotor 32, 33, 34, 35, 36, 37 Rolling bearings 41 Test equipment 42 Cathode tank 43 Electrolyte solution 44 cathode electrode 45 Anode tank 46 Electrolyte solution 47 Anode electrode 48 KCl saturated aqueous solution 49 Reference electrode 50 Salt Bridge 51 Test piece
Claims
1. A hard film-formed body having a hard film on a substrate surface that inhibits the intrusion and diffusion of hydrogen atoms, characterized in that: (A) the ratio of the Vickers hardness of the hard film to the Vickers hardness of the substrate is 0.90 to 1.20, or (B) The hard film has a thickness of 0.1 μm or more and less than 3 μm.
2. The hard film-forming body according to claim 1, characterized in that: When the above (A) is satisfied, the Vickers hardness of the substrate and the Vickers hardness of the hard film are respectively 500 Hv to 1000 Hv.
3. The hard film-forming body according to claim 1, characterized in that: The above-mentioned (A) is satisfied, and the hard film that suppresses the intrusion and diffusion of hydrogen atoms is a Ni film.
4. The hard film-forming body according to claim 3, characterized in that: The Ni coating includes a Ni-PB coating containing 90 mass % or more of Ni.
5. The hard film-forming body according to claim 1, characterized in that: In the electrochemical hydrogen permeation method using a test piece composed of the hard film-forming body (wherein the thickness of the substrate was 1 mm), the area of the test piece in contact with the electrolyte solution in the cathode tank and the anode tank was set to 3.14 cm 2 , set the current density on the anode tank side to 1 mA / cm 2 Electrolysis is performed, and at this time, the extended time of the penetration time of the test piece is 0.4 times or more of the penetration time of the target piece consisting of the substrate having a thickness of 1 mm.
6. The hard film-forming body according to claim 1, characterized in that: The above-mentioned (A) is satisfied, and an intermediate layer and a diamond-like carbon layer are formed on the surface of the hard film.
7. The hard film-forming body according to claim 1, characterized in that: Satisfying the above (A), the ratio of the Vickers hardness is 0.95 to 1.05, and the Vickers hardness of the substrate and the Vickers hardness of the hard film are 700 Hv to 800 Hv, respectively. The hard film for suppressing the intrusion and diffusion of hydrogen atoms is a Ni film, and the Ni film includes a Ni-PB film containing 90 mass % or more of Ni. An intermediate layer and a diamond-like carbon layer are formed on the surface of the hard film.
8. The hard film-forming body according to claim 1, characterized in that: The above-mentioned (B) is satisfied, and the hard film that suppresses the intrusion and diffusion of hydrogen atoms is a tungsten carbide film.
9. The hard film-forming body according to claim 8, characterized in that: The tungsten carbide film has a thickness of 0.2 μm or more and less than 1 μm.
10. A mechanical component, characterized in that The hard film-forming body according to claim 1 is used.
11. The mechanical component according to claim 10, characterized in that It is a bearing component.
12. A bearing, characterized in that: The bearing component according to claim 11 is used.
Citation Information
Patent Citations
Rolling bearing
JP2005069273A
Rolled component having long service life in hydrogen environment
JP2010043320A
Hydrogen embrittlement resistant material, and method for producing the same
JP2010174360A
